Magnetic proximity sensor based on magnetoelectric composites and printed coils - Pereira, Nélson (2020)
Magnetic sensors are mandatory in a broad range of applications nowadays, being the increasing interest on such sensors mainly driven by the growing demand of materials required by Industry 4.0 and the Internet of Things concept. Optimized power consumption, reliability, flexibility, versatility, lightweight and low-temperature fabrication are some of the technological requirements in which the scientific community is focusing efforts. Aiming to positively respond to those challenges, this work reports magnetic proximity sensors based on magnetoelectric (ME) polyvinylidene fluoride (PVDF)/Metglas composites and an excitation-printed coil. The proposed magnetic proximity sensor shows a maximum resonant ME coefficient (α) of 50.2 Vcm−1 Oe−1, an AC linear response (R2 = 0.997) and a maximum voltage output of 362 mV, which suggests suitability for proximity-sensing applications in the areas of aerospace, automotive, positioning, machine safety, recreation and advertising panels, among others.